Erosion of academic integrity in higher education system: symbolization of dishonesty - Nurshamimi Sabli; Nurhazrina Mat Rahim; Mohamad Ridhuan Mat Dangi; Nurhaiyyu Abdull Hamid; Mohd Fairuz Adnan; Roslan Abd Wahab; Noor Hasniza Haron (Penerbit Universiti Kebangsaan Malaysia, 2016)
Academic dishonesty has long been discussed in numerous researches and it has also become a common phenomenon worldwide. Most of these studies have examined the many forms of dishonesty and cheating behavior occurring in the academic field. These delinquent practices are very damaging as they, not only affect the educational system, but will also result in future problems during the students’ employment phase. This paper has investigated academic dishonesty through another angle by applying the concept of fraud triangle theory. The purpose of this study is to provide a general overview of academic dishonesty which symbolizes the pollution of academic integrity. This concept paper highlights the analysis of cheating in the Malaysian education context as well as in other countries globally. In addition, discussions on various definitions in relation to pollution of academic integrity have also been taken into consideration. The elements of fraud triangle theory have also been included through examining the causes or factors that lead to students’ cheating or academic dishonesty both in perception and real action. Further, the paper has also examined the various methods used in academic dishonesty and their implications to the educational system. Lastly, the preventive actions have also been discussed in the attempts to reduce the likelihood of cheating incidents.